Antinociceptive activity of Inula britannica L. and patuletin: In vivo and possible mechanisms studies. (12th June 2018) - Zarei, Mohammad; Mohammadi, Saeed; Komaki, Alireza
Abstract: Ethnopharmacological relevance: Inula britannica L. is a predominant medicinal plant traditionally utilized in the treatments of arthritis and back pain in Iranian folk medicine. Aim of the study: The purpose of this research was to evaluate the antinociceptive effects of Inula britannica L. flower essential oil (IBLEO) and one of its major constituents, Patuletin (Pn), in male mice. Materials and methods: In this study, we used pain assessment tests including acetic acid-induced writhing, tail-flick (TF), formalin induced paw licking (FIPL) model, and glutamate-induced paw licking (GPL). For understanding the supposed antinociceptive mechanisms of IBLEO, opioid andL -arginine/NO/cGMP/ KATP pathways were examined. Results: In the TF, writhing, GPL, and FIPL tests, a dosage of 100 mg/kg of IBLEO showed noteworthy antinociceptive effects in comparison with control (p < 0.05). In writhing test, administration of selective opioid antagonists (naltrindole, nor-binaltorphimine, and naloxonazine) attenuated the antinociceptive effect of IBLEO in comparison with control (p < 0.001). Both methylene blue and glibenclamide blocked the antinociceptive effect of IBLEO (p < 0.05), but the administration of L-arginine or sodium nitroprusside fundamentally potentiated the antinociception induced by IBLEO in phase II of the FIPL (p < 0.05). Additionally, patuletin showed significant antinociceptive effects in writhing, FIPL, and GPL tests (p < 0.01). Conclusion: The results of this examination showed that IBLEO and Pn have antinociceptive effects. The modulation of glutamatergic systems by opioid receptors could be involved, at least in part, in these effects. Our data also suggest the activation of theL -arginine/NO/cGMP/KATP pathway in IBLEO antinociceptive effects. Graphical abstract: fx1